Teaching Practices of EFL Teachers and the Enhancement of Creative Thinking Skills among Learners - Thouqan Saleem Masadeh (International Journal of Asian Education, 2021)
Development of students' creativity has been a prerequisite for the survival in this fast-changing technological age. Enhancement of learners' higher-order thinking skills should be the main concern of education systems around the world. Therefore, the present study aims to survey EFL teachers' knowledge about creative thinking, the activities they practice to enhance creative thinking skills. It also aims to understand EFL teachers' perceptions about the importance of creative thinking activities in promoting EFL learners' creativity. Moreover, it aims to check if there are significant differences between participants' perceptions due to teaching experience and stage. A total of 56 teachers took part in the present study through responding to a questionnaire developed to achieve the aims. Results revealed EFL teachers' lack of knowledge of creative thinking skills. Nevertheless, they showed that they "Often" practice creative thinking activities in classroom. Results also indicated that these activities were perceived "Important" for the enhancement of EFL learners' creative thinking skills.